Resveratrol Supplementation in Wet AMD: Association With Fewer Intravitreal Injections and Reduced Macular Fibrosis - Datseris I; Rouvas A; Tzanidaki ME; Kardara M; Geros V; Gouliopoulos N (Clinical Ophthalmology)
Ioannis Datseris,1 Alexandros Rouvas,2 Malvina-Efthymia Tzanidaki,1 Marina Kardara,1 Vasileios Geros,2 Nikolaos Gouliopoulos2 1Ophthalmology Department, Ophthalmological Institute “OMMA”, Athens, Greece; 2 2nd Department of Ophthalmology, Medical School of University of Athens, “attikon” University Hospital, Athens, GreeceCorrespondence: Ioannis Datseris, Ophthalmological Institute OMMA, Katehaki 74, Athens, 11525, Greece, Tel +302106755850, Fax +302106755851, Email jodats13@me.comPurpose: To evaluate the 2-year outcomes of resveratrol oral supplement given as an adjunctive treatment in patients with wet age-related macular degeneration (AMD) that were treated with intravitreal injections of aflibercept.Patients and Methods: In our retrospective study, 50 treatment-naïve patients suffering from wet-AMD were included. They were assigned to two subgroups of 25 patients each. Every participant was treated according to “Pro Re Nata” protocol; 3 monthly intravitreal injections of 2.0 mg aflibercept were applied followed by injections according to need. The patients in the second group also consumed daily two tablets of resveratrol enriched oral supplement (60 mg of resveratrol in total). For 2 years, the patients were monthly assessed with best corrected visual acuity (BCVA) measurement, fundus autofluorescence, optical coherence tomography (OCT) scans and OCT-angiography. The main endpoints were the change of BCVA, the number of anti-VEGF injections, the change of central foveal thickness values, and the expansion or new development of fibrosis.Results: Between the studied groups, no significant differences were detected in the baseline demographic and clinical data (p> 0.05 for all). Over the 24-month study period, both BCVA and central foveal thickness values did not differ significantly between the two groups. As for the number of applied injections, they were significantly fewer in the group of patients that were treated with the resveratrol supplement (9.32± 1.37 vs 7.40± 1.88, p< 0.001). Notably, the frequency of fibrosis progression was significantly lower in the resveratrol group (p=0.04).Conclusion: In conclusion, our findings suggest that resveratrol oral supplement could be considered as a useful adjunctive aid to the established treatment in cases suffering from wet AMD, highlighting the superiority of the combination treatment regimen, since it was accompanied by lower rates of both intravitreal aflibercept injections and progression of macular fibrosis.Keywords: wet AMD, Resvega, resveratrol, aflibercept, macular fibrosis, food supplement